Prevalence of Kennedy Classification in Partially Edentulous Patients - A Retrospective Study - Tulsani Minal Gopal, Subhashree. R (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the study is to evaluate the prevalence of partial edentulism according to Kennedy’s classificationin the South Indian population. A retrospective study was done in which 1419 removable partial dentureswere fabricated from 1 June 2019 till 1 March 2020 were included. Data was reviewed from the patientsrecords and analysed the data of 86,000 patients between June 2019 and March 2020 that were documentedin a private institution. The data was analyzed using descriptive statistics and Chi square test and pearsoncorrelation was done for checking correlation between age, gender and type of classification. Out of 1419removable partial dentures, 58.4% were fabricated for males. Class III had the highest prevalence overalland in males and females. There was no significant relation between the type of Kennedy classification ofpartially edentulous patients with age and gender. Prevalence of Kennedy’s Class III was the most commonin the South Indian population. The prevalence was more in patients above 50 years of age. Male had moreprevalence than females. Gender and age did not affect the prevalence of types of Kennedy’s classes.